Hypermethylation of Cox5a promoter is associated with mitochondrial dysfunction in skeletal muscle of high fat diet-induced insulin resistant rats. - Ying-ying Gong; Yuan-yuan Liu; Jin Li; Lei Su; Shuang Yu; Xiao-nan Zhu; Xiao-pei Cao; Hai-peng Xiao (PLoS ONE, 2014)
High-fat diet (HFD) is an environmental factor that contributes to the pathogenesis of obesity and type 2 diabetes. A number of genes influencing oxidative phosphorylation (OXPHOS) were found to be downregulated in skeletal muscle of humans and rats treated with HFD and have been implicated in mitochondrial dysfunction, insulin resistance, and consequent type 2 diabetes. In this study, we hypothesized that DNA methylation plays a crucial role in the regulation of OXPHOS genes in skeletal muscle of rats exposed to HFD. Using whole genome promoter methylation analysis of skeletal muscle followed by qPCR and bisulfite sequencing analysis, we identified hypermethylation of Cox5a in HFD rats. Furthermore, we found that Cox5a hypermethylation was associated with downregulation of Cox5a expression at the mRNA and protein level, and a reduction in mitochondrial complex IV activity and ATP content in HFD-induced insulin resistant rats compared to controls. Moreover, we found that while exposure to palmitate resulted in hypermethylation of the Cox5a promoter in rat myotubes, demethylation with 5-aza-2'-deoxycytidine was associated with preserved Cox5a expression, as well as restoration of complex IV activity and cellular ATP content. These novel observations indicate that Cox5a hypermethylation is associated with mitochondrial dysfunction in skeletal muscle of HFD-induced insulin resistant rats.